Possible Impact of Comorbid Conditions on the Persistence of Nocturnal Enuresis: Results of a Long-Term Follow-up Study - Ferrara, Pietro; De Angelis, Maria Chiara; Caporale, Olga; Malamisura, Monica; Del Volgo, Valentina; Vena, Flaminia; Gatto, Antonio; Chiaretti, Antonio (Urology Journal, 2014)
Purpose: To describe the natural history of patients with nocturnal enuresis (NE) during a 10-year period and to evaluate possible impact of comorbid conditions on the persistence of NE. Materials and Methods: Ninety-five children (male to female ratio [M:F] 65:30), aged at first visit between 6 and 21 years were included in this study. Of study subjects 75 had primary monosymptomatic nocturnal enuresis (PMNE), 3 had secondary monosymptomatic nocturnal enuresis (SMNE) and 17 had non-monosymptomatic nocturnal enuresis (NMNE). Demographic and NE-related details were assessed from electronic medical records and by telephone interview at the times 3, 6, 12 months and 3, 5, 10 years after the first examination. Sixty-seven of 95 patients were enrolled, of whom 57 had PMNE (M:F ratio 39:18, mean age 9.35 ± 2.81 years, mean age at improvement 11.5 ± 4.08 years), 8 had NMNE (M:F ratio 4:4, mean age 10.1 ± 2.64 years, mean age at improvement 12.6 ± 1.68 years) and 2 had SMNE (M:F ratio 1:1, mean age 12 years, mean age at improvement 13.5 ± 2.12 years). Results: The mean duration of follow up was 7.2 ± 2.5 years. All of the 67 children had 5 years follow up. Only 29 of 67 patients (19 with PMNE, 8 with NMNE and 2 with SMNE) had 10 years follow up and 4 of 19 with PMNE were still affected by NE. Out of 57 patients with PMNE 12 (2/12 with language disorders, 1/12 varicocele and 1/12 cryptorchidism) and out of 8 patients with NMNE 1 were still enuretic while all patients with SMNE were in remission. Conclusion: We observed that language disorders and testicular pathology in NE children could be comorbidities associated with persistence of NE and treatment resistance.